Vacuolar sequestration capacity and long-distance metal transport in plants - Peng, Jiashi; Gong, Jiming (Frontiers in Plant Science, 2014)
The vacuole is a pivotal organelle functioning in storage of metabolites, mineral nutrients and toxicants in higher plants. Accumulating evidence indicates that in addition to its storage role, the vacuole contributes essentially to long-distance transport of metals, through the modulation of Vacuolar Sequestration Capacity (VSC) which is shown to be primarily controlled by cytosolic metal chelators and tonoplast-localized transporters, or the interaction between them. Plants adapt to their environments by dynamic regulation of VSC for specific metals and hence targeting metals to specific tissues. Study of VSC provides not only a new angle to understand the long-distance transport of minerals in plants, but also an efficient way to biofortify essential mineral nutrients or to phytoremediate non-essential metal pollution. The current review will focus on the most recent proceedings on the interaction mechanisms between VCS regulation and long-distance metal transport.